Antibiotic activity the minero-medicinal water of "Sta. Cruz de las Salinas" lagoon, Chilca, Lima - Chacón Roldán, Gloria (1980)
The author presents the study of the bactericidal activity in vitro and in vivo of the minero-medicinal water of the Santa Cruz de las Salinas lagoon, Chilca, on So/mone/Ia typhi. Investigations made during the period February 1977-July 1979 at the Health fnstitute, Lima, have proved that this water exerts bacteriostatic and bactericidal action on a highly pathogen germ for human organism of Gram negative type (strain SalmonelIa typhy TY2). Tryals of toxicity of this water in the animal organism have been made inoculating two groups of mice by intravenous and intraperitoneal way, demostrating that it does not exert toxic actión, althoug it produces a stimulant actioll on the blood cells.